2008
DOI: 10.1007/s10620-008-0569-3
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Lithium on Acetic Acid-Induced Colitis in Rats

Abstract: Inflammatory bowel disease (IBD) is a multifactorial disease with unknown etiology characterized by oxidative stress, leukocyte infiltration, and rise in inflammatory cytokines such as tumor necrosis factor (TNF-alpha). Lithium, as a therapeutic agent for bipolar disorder, exerts some anti-inflammatory properties. In this study we have investigated the effects of lithium on acetic-acid-induced colitis in rats. Lithium (5, 10, and 20 mg/kg) was administered 1 h before the introduction of acetic acid. Colonic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 41 publications
(39 reference statements)
2
14
0
Order By: Relevance
“…On the 8th day, animals were sacrificed, the colons removed, and scored macroscopically such that the score 0 described normal appearance with no damage while scores 5–8 were an extensive damage more than 2 cm in length [11]. Colons were cut longitudinally into 2, one for histopathologic scoring from 0 (no damage) to 4 (widespread necrosis with massive neutrophil infiltration and hemorrhage) [11] and one for measuring biochemical markers including myeloperoxidase activity – an indicator of leukocyte infiltration [12], malondialdehyde‐showing lipid peroxidation [13], tumor necrosis factor‐alpha (TNF‐α) [11], and interleukin‐1β (IL‐1β) [11]. Macroscopic and histologic scorings were performed by investigators blinded to the experimental groups.…”
Section: Methodsmentioning
confidence: 99%
“…On the 8th day, animals were sacrificed, the colons removed, and scored macroscopically such that the score 0 described normal appearance with no damage while scores 5–8 were an extensive damage more than 2 cm in length [11]. Colons were cut longitudinally into 2, one for histopathologic scoring from 0 (no damage) to 4 (widespread necrosis with massive neutrophil infiltration and hemorrhage) [11] and one for measuring biochemical markers including myeloperoxidase activity – an indicator of leukocyte infiltration [12], malondialdehyde‐showing lipid peroxidation [13], tumor necrosis factor‐alpha (TNF‐α) [11], and interleukin‐1β (IL‐1β) [11]. Macroscopic and histologic scorings were performed by investigators blinded to the experimental groups.…”
Section: Methodsmentioning
confidence: 99%
“…Acetic acid-induced colitis is a model of IBD that bears close resemblance to human IBD in terms of pathogenesis, histopathological features and inflammatory mediator profile [37,92,93,94,95,96]. Intrarectal administration of dilute solution of acetic acid causes non-transmural inflammation characterized by increased neutrophil infiltration into the intestinal tissue, massive necrosis of mucosal and submucosal layers, vascular dilation, edema and submucosal ulceration that are noteworthy features of human colitis [49,94,96,97,98]. It has been anticipated that the protonated form of the acid liberates protons within the intracellular space that possibly causes massive intracellular acidification resulting in immense epithelial damage.…”
Section: Chemical Induced Models Of Chronic Intestinal Inflammationmentioning
confidence: 99%
“…Subsequently, using a medical-grade polyurethane tube for enteral feeding (external diameter 2 mm), 1~2 ml of (3~4%) acetic acid is instilled 6~8 cm proximal to the anus verge. Eventually, after 15~30 s of exposure the fluid is withdrawn and animals are sacrificed and their blood and colons are collected 24~48 hrs after induction of colitis for carrying out various histopathological and biochemical investigations [25,26,89,97,106,107,108]. Other scientists have revealed that intracolonic administration of 4 ml of 4 % acetic acid at a dose 5 ml/kg also leads to induction of colitis in rats [99,109,110,111,112].…”
Section: Chemical Induced Models Of Chronic Intestinal Inflammationmentioning
confidence: 99%
“…It has been suggested that lithium may suppress viral infection 10,11 and exerts protective effects in a murine model of systemic lupus erythematosus 12 . Moreover, our group has recently showed beneficial properties for lithium on acetic acid induced colitis in rats 13 . In spite of accumulating data regarding anti‐inflammatory actions of lithium; its precise mechanism of action is yet to be determined.…”
Section: Introductionmentioning
confidence: 99%